Prognostic score for life expectancy evaluation of lung cancer patients after bone metastasis - Dumnoensun Pruksakorn (2018)
© 2017 The Authors Background This study identifies the overall survival status of lung cancer patients with bone metastasis and metastasis patterns. Poor prognostic factors were identified to develop a scoring system for estimating survival period after bone metastasis. Methods A retrospective cohort analysis was performed at Chiang Mai University for the period January 1, 2006 and December 31, 2013. Time-to-event analysis was performed to estimate survival rate. The primary end point was death related to lung cancer. Univariate and multivariate analysis of the prognostic variables was done using the Cox's regression model. The score was derived from the corresponding estimated regression coefficients of significantly poor prognostic factors. Results A total of 505 lung cancer with bone metastasis patients were analyzed. Four hundred two cases (79.6%) were concurrent diagnosis and 103 (20.4%) were subsequent diagnosis. The median survival time of lung cancer after bone metastasis 148 days. Male gender and ECOG 3–4 were significant poor prognostic factors for lung cancer after bone metastasis, with hazard ratios of 1.42 (95% CI 1.17–1.73), and 1.30 (95% CI 1.06–1.60), respectively. Prognosis score was determined using the binary term present/not-present for those factors. The curve from prognostic score summations of 2, 1 and 0 presented a good discrimination of survival expectancy, showing an expected median survival time of approximately 109, 146, and 225 days, respectively. Conclusions Prognostic score is a clinically simple and easy method for estimating life expectancy and for guiding interventions in bone metastasis of lung cancer.